Literature Review: The Effect of Audio Hypnobirthing on Anxiety Levels in First Childbirth Mothers - Dwi Nur Octaviani Katili; Siskawati Umar; Saras Dwiyanti Nteya (PSPP JOURNALS, 2021)
Anxiety in childbirth is a response to certain threatening situations, often anxiety can be characterized by feelings of irritability, anxiety, nervousness, excessive vigilance, and feelings of tension when facing the labor process. Maternal mothers who cannot control their anxiety and fear before giving birth will release high amounts of catecholamine hormones. Stress hormones that are produced in excess in pregnant women can interfere with the blood supply to the fetus and can make the fetus hyperactive. This literature study aims to determine the effect of audio hypnobirthing on maternal anxiety levels. This study uses a descriptive narrative method in the form of a literature study, literature searches are carried out through Google Scholar, Indonesia One Search (IOS), Digital Reference Garba (GARUDA) and text books. The literature used is published in 2011-2020 both nationally and internationally and is relevant to the topic taken. The results of the study of literature in 6 journals and 3 books found that there was an effect of audio hypnobirthing on the anxiety level of maternity mothers. Based on the results of the study, it can be concluded that hypnobirthing can prevent anxiety in maternity.